Attachment in Middle Childhood: Progress and Prospects. Issue 148 (June 2015) - Bosmans, Guy; Kerns, Kathryn A.
Abstract: Contrary to the substantial amount of research on infant, preschool, adolescent, and adult attachment, middle childhood has long been neglected by the international attachment research community. In the past two decades, however, there has been a steep increase in research focusing on middle childhood attachment. This article provides an overview of past research, with a focus on the characteristics of secure versus insecure attachment at this age period, and an understanding of the different approaches to measure attachment. The article demonstrates the relevance of past middle childhood attachment research for both developmental psychologists and clinicians trying to understand the importance of middle childhood in individuals' development across the life span. © 2015 Wiley Periodicals, Inc.